Chest Image Staging and Prevalence of Current Smoking Among Hospitalized COVID-19 Patients in Turkey - Eroğlu, Sinan; Şahin, Eren; Nurdan Yoluç, Şule; Eroğlu, Yasemin; Aydoğdu, İmran (ENT Updates, 2022)
Objective: Novel coronavirus disease is a new infectious agent of the respiratory tract characterized by severe acute respiratory syndrome. For this disease, there are limited data with regard to the clinical characteristics of the patients and prognostic factors. Methods: We collected data from 213 patients who were hospitalized intoCOVID-19 isolation with positive PCR test results. We recorded various patient val- ues, including blood test results. We also noted age, gender, additional diseases, dura- tion of discharge, whether they live or die, whether they smoke, and their radiological staging. Results: In CT imaging with a staging of maximum 4 points and minimum 0 points, the mean value resulted in 1.95. The average radiological stage of the dead patients' group was reported as 2.56. There was a correlation between the radiological predictor andthe outcome status (P = .002). The number of smokers was 14 (6.5%). Of the 26 patientswho died, 3 were smokers and 23 were non-smokers. Conclusion: Fourteen patients in the study were smokers. While in COVID-19 isola-tion service, only a small rate of smoking was observed. That supports the theory that smoking has no negative impact on COVID-19 development. There was also a corre- lation between the radiological predictor and the outcome status. It seems that an elevated radiological stage is a predictor of death.